2021
DOI: 10.31557/apjcp.2021.22.11.3685
|View full text |Cite
|
Sign up to set email alerts
|

ABO Blood Group Differentials on Survival in Hepatocellular Carcinoma Patients Treated with Chemoembolization

Abstract: Background:The association between ABO blood group and the prognosis of hepatocellular carcinoma (HCC) remains unclear. We investigated the impact of ABO blood groups as a prognostic factor in HCC patients treated with transarterial chemoembolization (TACE). Materials and methods: We revisited records of all HCC patients who underwent TACE between January 2007 and December 2019 at a tertiary care hospital. The inclusion criteria were HCC patients, Child-Pugh score A5-B7, and treated with TACE monotherapy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In another study in 2022, K Mohkam et al [ 32 ], by examining the effect of ABO blood group type on liver cancer recurrence after liver transplantation on 925 patients with HCC, showed that the 5-year survival and recurrence rate in patients with Blood type A was significantly higher than patients with non-A blood type, which was consistent with the results of our study. In another study, K Bannangkoon et al [ 35 ] evaluated the effect of ABO blood group type on the survival of patients with HCC treated with embolization. They showed that the patients with blood type O compared to non-O had a significantly higher survival rate, confirming our study’s results.…”
Section: Discussionmentioning
confidence: 99%
“…In another study in 2022, K Mohkam et al [ 32 ], by examining the effect of ABO blood group type on liver cancer recurrence after liver transplantation on 925 patients with HCC, showed that the 5-year survival and recurrence rate in patients with Blood type A was significantly higher than patients with non-A blood type, which was consistent with the results of our study. In another study, K Bannangkoon et al [ 35 ] evaluated the effect of ABO blood group type on the survival of patients with HCC treated with embolization. They showed that the patients with blood type O compared to non-O had a significantly higher survival rate, confirming our study’s results.…”
Section: Discussionmentioning
confidence: 99%